2007
DOI: 10.1002/hep.21827
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and natural course of fatty liver in the general population: The Dionysos study

Abstract: Using the general population of the Dionysos Study, we followed up 144 subjects without fatty liver (FL ؊ ) and 336 with fatty liver (FL ؉ ) for a median time of 8.5 years. All subjects had suspected liver disease (SLD) defined as altered liver enzymes, high mean corpuscular volume, or low platelet count in the absence of HBV and HCV infection. Ethanol intake was assessed using a food frequency questionnaire, and FL was diagnosed using ultrasonography. The incidence and remission rates of FL were 18.5 and 55.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
134
5
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(159 citation statements)
references
References 51 publications
(37 reference statements)
12
134
5
8
Order By: Relevance
“…In severe cases, NASH can progress to either cirrhosis or liver cancer. Estimates of NAFLD prevalence range from 22 to 33.6% in the U.S. population, and similar estimates have recently been found among adults in Western Europe [10]. Estimates of NASH prevalence range from 2 to 5.7%, but may be found in more than 25% of obese individuals [9].…”
Section: Non-alcoholic Fatty Liver Disease (Nafld)supporting
confidence: 64%
“…In severe cases, NASH can progress to either cirrhosis or liver cancer. Estimates of NAFLD prevalence range from 22 to 33.6% in the U.S. population, and similar estimates have recently been found among adults in Western Europe [10]. Estimates of NASH prevalence range from 2 to 5.7%, but may be found in more than 25% of obese individuals [9].…”
Section: Non-alcoholic Fatty Liver Disease (Nafld)supporting
confidence: 64%
“…Over a follow up of 8.5 years, the incidence of ultrasonographically detected NAFLD was 18.5 per 1,000 person years in a sample representative of the general Italian population 36 . Data gathered in the past few years are clarifying the natural history of histologically diagnosed NAFLD.…”
Section: Incidence Of Nafld and Future Projections In Europementioning
confidence: 97%
“…The two major available studies, conducted on a large cohort of Italian patients with T2DM, reported NAFLD prevalence of 60-70% 33,34 ; data from the UK suggests that NAFLD, detected ultrasonographically, is present in 42.6% of patients with T2DM 35 . Prevalence of NAFLD also increases with BMI, such that in an unselected Italian population sample 91% of patients who were obese (BMI ≥30 kg/m 2 ), 67% of those who were overweight (BMI 25-30 kg/m 2 ) and 25% of individ uals at a normal weight (BMI 18-25 kg/m 2 ) had ultra sonographical evidence of NAFLD 36 . The prevalence of NAFLD among patients matching at least one of the Adult Treatment Panel III (ATP III) criteria for serum lipid level alterations is similarly high at 78.8% 33 .…”
Section: Nafld In Europementioning
confidence: 99%
“…Metabolically induced liver disease may also act as a contributing factor in the progression of liver disease of a different aetiology [5,10]. Because of the high prevalence of metabolic diseases in the adult population, there is a frequent chance association, and there is evidence that the progression of viral or genetic liver diseases may be more severe in individuals with steatosis, leading to an underestimation of the overall clinical impact of NAFLD on morbidity and mortality [5,10].…”
Section: Epidemiology and Natural History Of Nafldmentioning
confidence: 99%
“…Population and cohort-based studies suggested that the regular course is relatively benign in pure steatosis [10,11], with a long-term prognosis similar to that for the general population [11]. However, a few clinical series observed that hepatic steatosis is a risk factor for NAFLD progression, mainly in the presence of obesity and type 2 diabetes [12].…”
Section: Epidemiology and Natural History Of Nafldmentioning
confidence: 99%